Leisure-time physical activity and lung cancer risk: A systematic review and meta-analysis. (May 2016) - Brenner, Darren R.; Yannitsos, Demetra H.; Farris, Megan S.; Johansson, Mattias; Friedenreich, Christine M.
Highlights: Physical activity was associated with reduced lung cancer risk among current and former smokers. Effects were consistent across, histology groups and geographic location of studies. The method and duration of physical activity assessment impacted the heterogeneity of effects observed across studies. Additional research is needed among never smokers to further evaluate the potential for confounding in this association. Abstract: Objectives: We conducted a systematic review and meta-analysis of the association between recreational physical activity and lung cancer risk to update previous analyses and to examine population subgroups of interest defined by smoking status and histology. Materials and methods: We searched the PubMed database for studies up to May 2015. Individual study characteristics were abstracted including study design, number of cases, assessment of recreational physical activity and type and level of adjustment for confounding factors. Combined effect estimates were calculated for the overall associations and across subgroups of interest. Results: We identified 28 studies that were eligible for inclusion in the meta-analysis. The overall analysis indicated an inverse association between recreational physical activity and lung cancer risk (Relative Risk (RR), 0.76; 95% Confidence Interval (CI), 0.69–0.85, p-value: <0.001). Similar inverse associations with risk were also noted for all evaluated histological subtypes, including adenocarcinoma (RR, 0.80; 95% CI, 0.72–0.88), squamous (RR, 0.80; 95% CI, 0.71–0.90) and small cell (RR, 0.79; 95% CI, 0.66–0.94). When we examined effects by smoking status, inverse associations between recreational physical activity and lung cancer risk were observed among former (RR, 0.77; 95% CI, 0.69–0.85) and current smokers (RR, 0.77; 95% CI, 0.72–0.83), but not among never smokers (RR, 0.96; 95% CI, 0.79–1.18). Conclusion: Results from this meta-analysis suggest that regular recreational physical activity may be associated with reduced risk of lung cancer. Only four studies examining never smokers were identified, suggesting the need for additional research in this population.